Improving Speaking Skill Through Mobile-Assisted Language Learning (MALL) - Darmawati, Darmawati (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2018)
Technology plays important role in education these days, it has changed teaching and learning languages. Mobile Assisted Language Learning (MALL)  plays crucial roles in this field. The focus of this study is to find out how effective to use MALL to help students to improve their English speaking skill. This study, therefore, aims at improving studentsâ€™ speaking ability through Mobileâ€“Assisted Language learning. This study was a classroom action research, which was carried out in three cycles. The participants of the research were second semester of computer science students in Pamulang University. Based on the findings, it showed that Mobile-Assisted Language Learning could improve studentsâ€™ speaking ability in terms of pronunciation, grammar, vocabulary, fluency, and comprehension. The more the students practice their speaking though MALL the better their speaking ability.